Surface Deformation Monitoring Using Time-lapse Microgravity Method in Central and East Lombok Regencies - Suhayat Minardi; Teguh Ardianto; Alfina Taurida Alaydrus (Indonesian Journal of Physics, 2020)
Surface deformation is a natural occurrence on the surface of the earth. The deformation can be in the form of subsidence or uplifting of the land surface. In this research, an time-lapse microgravity method will be applied to monitor surface deformation that occurs in Central Lombok and East Lombok Districts. The method of time-lapse microgravity is repetitive gravity measurement at the same point with a certain time interval, the measured magnitude is a change in the value of the acceleration of gravity and the microGal scale. Measurements were made in August 2016, April 2018, and June 2019. The measured value of the change in gravitational acceleration is the superposition of the changes caused by subsurface and surface sources. Separation of the two values is carried out using striping filter, which takes into account the ratio of density, thickness, and depth of the surface and subsurface layers. Land subsidence occurred during the period August 2016 to April 2018 and land uplifting occurred during the April 2018 to June 2019 period. This land subsidence occurred due to natural compacting and minor tectonic activity (small earthquakes that were not felt) while land uplifting was occurred due to major tectonic activities, in the form of the Lombok Earthquake in July to September 2018.